Laminated coil component
By designing a resin paste layer and a conductive paste layer in the laminated coil component and forming the first and second voids, the crack problem caused by the increase in stress during the calcination process is solved, and the reliability of the component is improved.
Patent Information
- Application Number
- CN202411925083.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2020-02-06
- Filing Date
- 2021-02-04
- Publication Date
- 2025-04-25
AI Technical Summary
During the calcination process, the existing laminated coil components have different rebound amounts of the resin layer than the insulating layer, which leads to increased stress, which may cause cracks and reduced reliability.
A resin paste layer and a conductive paste layer are formed on the insulating sheet, and an extension is formed at a specific position of the conductive paste layer, and the first and second voids are formed by lamination and calcination, thereby reducing stress between the coil conductor layer and the insulator portion.
By designing the first and second voids in the laminated coil component, stress concentration during calcination is reduced, cracks occur, and component reliability is improved.
Smart Images

Figure CN119889884A_ABST
Abstract
Description
This application is a divisional application of the application with application number 2021 1 0153 812.X, application date February 4, 2021, and invention name “Laminated coil component” Technical Field The present disclosure relates to a laminated coil component. Background Art As a method for manufacturing a laminated coil component, there is known a method of forming a coil pattern on an insulating sheet, laminating them to obtain a laminated molded body, and calcining the laminated molded body. At this time, in order to relax the stress between the coil and the insulating layer, a gap is often provided between the coil and the insulating layer (Patent Document 1). Patent Document 1: Japanese Patent Application Publication No. 2018-11014 In the laminated coil component described in Patent Document 1, the void extends outward from the side of the coil conductor. The extended portion of the void is formed by forming a resin layer at the location where the void is provided and eliminating the resin layer by calcination. During calcination, the laminate is crimped, but the amount of springback of the resin layer during crimping is different from that of other insulating layers, so stress is generated, which may cause cracks in the component and reduce reliability. Summary of the invention An object of the present disclosure is to provide a laminated coil component with high reliability. The present disclosure includes the following aspects.
[0001] A method for manufacturing a laminated coil component is provided. The stacked coil component includes: an insulator portion; a coil embedded in the insulator portion and electrically connected by a plurality of coil conductor layers; and an external electrode disposed on a surface of the insulator portion and electrically connected to the coil, a first gap portion being provided between the insulator portion and a main surface of the coil conductor layer, and a second gap portion extending horizontally outward from a side surface of the coil conductor layer at the same height as the first gap portion, The manufacturing method of the laminated coil component comprises the following steps: Prepare insulation sheets; forming a resin paste layer on the insulating sheet using a resin paste; forming a conductive paste layer using a conductive paste, the conductive paste layer covering the resin paste layer and having a protruding portion at a location where the second gap is formed; forming an insulating paste layer on the insulating sheet using an insulating paste so that at least a portion of the upper surface of the conductive paste layer is exposed; A plurality of insulating sheets formed with the above-mentioned layers are stacked to form a stacked molded body in which the conductive paste layers are connected in a coil shape; The above-mentioned stacked compact is calcined.
[0002] According to the production method described in the above [1], the PVC of the above conductive paste is 60% or more and 80% or less.
[0003] The production method according to [1] or [2], wherein the conductive paste is a silver paste.
[0004] According to the manufacturing method described in any one of [1] to [3], the thickness of the extension portion is 1.0 μm or more and 10.0 μm or less.
[0005] According to the manufacturing method described in any one of [1] to [4], the width of the protruding portion is 1.0 μm or more and 30.0 μm or less.
[0006] According to the manufacturing method described in any one of [1] to [5] above, the extended portion has a tapered shape toward the outside of the conductive-paste layer.
[0007] According to the production method described in any one of [1] to [6] above, the conductive paste layer having the protruding portion is formed using a printing plate.
[0008] Provided is a laminated coil component, comprising: an insulator portion; a coil embedded in the insulator portion and formed by electrically connecting a plurality of coil conductor layers; and an external electrode disposed on a surface of the insulator portion and electrically connected to the coil. A first gap is provided between the insulator portion and the main surface of the coil conductor layer. A second gap portion is provided at the same height as the first gap portion and extends outward in the horizontal direction from the side surface of the coil conductor layer.
[0009] According to the laminated coil component described in the above [8], the thickness of the coil conductor layer is not less than 1.0 μm and not more than 90.0 μm.
[0010] According to the laminated coil component described in [8] or [9] above, the ratio of the width of the first gap to the width of the coil conductor layer is greater than or equal to 0.1 and less than or equal to 0.9.
[0011] According to the laminated coil component described in any one of [8] to
[10] , the thickness of the first gap portion is not less than 1.0 μm and not more than 10.0 μm.
[0012] According to the laminated coil component described in any one of [8] to
[11] , the thickness of the second gap portion is not less than 1.0 μm and not more than 10.0 μm.
[0013] According to the laminated coil component described in any one of [8] to
[12] , the width of the second gap is not less than 1.0 μm and not more than 30.0 μm.
[0014] According to the laminated coil component described in any one of [8] to
[13] , the second gap has a tapered shape extending from the coil conductor layer toward the outside. The method for manufacturing a laminated coil component disclosed in the present invention is unlikely to cause problems due to springback during manufacturing, and thus can provide a laminated coil component with high reliability. BRIEF DESCRIPTION OF THE DRAWINGS Figure 1 1 is a perspective view schematically showing a laminated coil component 1 according to the present disclosure. Figure 2 Yes means Figure 1 2 is a cross-sectional view of the laminated coil component 1 along the cutting plane xx. Figure 3 yes Figure 1 1 is a cross-sectional view of the coil conductor layer 15 , the first gap portion 21 , and the second gap portion 22 of the laminated coil component 1 . Figure 4 (a) to (e) are used to Figure 1 FIG. 2 is a diagram for explaining a method for manufacturing a laminated coil component 1 shown in FIG. Figure 5 (a), (b), (d) and (e) are related to Figure 4 (a), (b), (d) and (e) corresponding cross-sectional views. Figure 6 (a) to (d) are used to Figure 1 FIG. 2 is a diagram for explaining a method for manufacturing a laminated coil component 1 shown in FIG. Figure 7 (a) to (d) are used to Figure 1 FIG. 2 is a diagram for explaining a method for manufacturing a laminated coil component 1 shown in FIG. Figure 8 (a) to (e) are used to Figure 1 FIG. 2 is a diagram for explaining a method for manufacturing a laminated coil component 1 shown in FIG. Description of Reference Numerals 1…laminated coil component; 2…base; 4, 5…external electrodes; 6…insulator portion; 7…coil; 11…first insulator layer; 12…second insulator layer; 15…coil conductor layer; 21…first gap portion; 22…second gap portion; 31…ferrite sheet; 32…resin paste layer; 33…low shrinkage conductive paste layer; 34…high shrinkage conductive paste layer; 35…ferrite paste layer; 36…extending portion; 41…ferrite sheet; 42…conductive hole; 43…resin paste layer; 44…high shrinkage conductive paste layer; 45…ferrite paste layer; 51…ferrite sheet; 52…conductive hole; 53…resin paste layer; 54…high shrinkage conductive paste layer; 55…ferrite paste layer; 61…ferrite sheet; 62…conductive hole; 63…resin paste layer; 64…low shrinkage conductive paste layer; 65…high shrinkage conductive paste layer; 66…ferrite paste layer. DETAILED DESCRIPTION Hereinafter, the present disclosure will be described in detail with reference to the drawings. However, the shapes and arrangements of the laminated coil component and each component of the present embodiment are not limited to the examples shown in the drawings. Figure 1 A perspective view showing a laminated coil component 1 according to this embodiment, Figure 2 Indicates xx cross-sectional view. In addition, Figure 3 express Figure 2 However, the shapes and arrangements of the laminated coil components and the components of the following embodiments are not limited to the examples shown in the drawings. like Figure 1 to Figure 3 As shown in FIG. 1 , the laminated coil component 1 of the present embodiment is a laminated coil component having a substantially rectangular parallelepiped shape. Figure 1 The surface perpendicular to the L axis is called the "end face", the surface perpendicular to the W axis is called the "side face", and the surface perpendicular to the T axis is called the "upper and lower face". The stacked coil component 1 generally includes a substrate 2 and external electrodes 4 and 5 provided on the two end faces of the substrate 2. The substrate 2 includes an insulator portion 6 and a coil 7 buried in the insulator portion 6. The insulator portion 6 has a first insulator layer 11 and a second insulator layer 12. The coil 7 is formed by being connected into a coil shape through a coil conductor layer 15 using a via conductor (not shown) that penetrates the first insulator layer 11. The coil 7 is connected to the external electrodes 4 and 5 at the lead portions provided at its two ends. On the main surface of the insulator portion and the coil conductor layer 15 (on Figure 2 and Figure 3 A first gap 21 is provided between the first insulating layer 11 and the coil conductor layer 15. In addition, a second gap 22 extending horizontally outward from the side surface of the coil conductor layer is provided at the same height as the first gap. Hereinafter, a method for manufacturing the laminated coil component 1 according to the present embodiment described above will be described. In the present embodiment, a mode in which the insulator portion 6 is formed of a ferrite material will be described. (1) Preparation of ferrite paste First, a ferrite material is prepared. The ferrite material contains Fe, Zn and Ni as main components, and further contains Cu as needed. Usually, the main components of the ferrite material are substantially composed of oxides of Fe, Zn, Ni and Cu (ideally Fe2O3, ZnO, NiO and CuO). As ferrite materials, Fe2O3, ZnO, CuO, NiO and components added as needed are weighed to a predetermined composition, mixed and crushed. The crushed ferrite material is dried, and calcined at a temperature of, for example, 700 to 800°C to obtain a calcined powder. A ferrite paste can be prepared by adding a predetermined amount of solvent (ketone solvent, etc.), resin (polyvinyl acetal, etc.) and plasticizer (alkyd plasticizer, etc.) to the calcined powder, kneading them using a planetary mixer, and further dispersing them using a three-roll mill, etc. (2) Preparation of ferrite sheets Next, an organic binder such as polyvinyl butyral and an organic solvent such as ethanol and toluene are added to the calcined powder of the ferrite material obtained in the same manner as above, and the resulting mixture is put into a pot mill together with PSZ balls for mixed pulverization. The obtained mixture can be molded into a sheet of a specified thickness, size, and shape by a scraper method or the like to produce a ferrite sheet. In the above-mentioned ferrite material, the Fe content converted into Fe2O3 may preferably be 40.0 mol% or more and 49.5 mol% or less (based on the total of main components, the same applies hereinafter), and more preferably 45.0 mol% or more and 49.5 mol% or less. In the above ferrite material, the Zn content may be preferably 5.0 mol % or more and 35.0 mol % or less (based on the total of main components, the same applies hereinafter), and more preferably 10.0 mol % or more and 30.0 mol % or less, calculated as ZnO. In the ferrite material, the Cu content is preferably 4.0 mol % to 12.0 mol % (based on the total of main components, the same applies hereinafter), and more preferably 7.0 mol % to 10.0 mol % in terms of CuO. In the above-mentioned ferrite material, the Ni content is not particularly limited, and may be the remainder of the above-mentioned other main components, namely, Fe, Zn, and Cu. In one embodiment, in the above-mentioned ferrite material, Fe is converted into Fe2O3 of 40.0 mol% or more and 49.5 mol% or less, Zn is converted into ZnO of 5.0 mol% or more and 35.0 mol% or less, Cu is converted into CuO of 4.0 mol% or more and 12.0 mol% or less, and NiO is the remainder. In the present disclosure, the above-mentioned ferrite material may further contain additives. Examples of additives in the ferrite material include, but are not limited to, Mn, Co, Sn, Bi, and Si. The content (addition amount) of Mn, Co, Sn, Bi, and Si is preferably 0.1 parts by weight or more and 1 part by weight or less, respectively, relative to a total of 100 parts by weight of the main components (Fe (converted into Fe2O3), Zn (converted into ZnO), Cu (converted into CuO), and Ni (converted into NiO)). In addition, the above-mentioned ferrite material may further contain impurities that are unavoidable in manufacturing. In addition, it can also be considered that the Fe content (calculated as Fe2O3), Mn content (calculated as Mn2O3), Cu content (calculated as CuO), Zn content (calculated as ZnO) and Ni content (calculated as NiO) in the sintered ferrite are substantially no different from the Fe content (calculated as Fe2O3), Mn content (calculated as Mn2O3), Cu content (calculated as CuO), Zn content (calculated as ZnO) and Ni content (calculated as NiO) in the ferrite material before calcination. (3) Preparation of Conductive Paste for Coil Conductor First, a conductive material is prepared. As the conductive material, for example, Au, Ag, Cu, Pd, Ni, etc. can be listed, preferably Ag or Cu, more preferably Ag. The conductive paste for coil conductor can be prepared by weighing a predetermined amount of powder of the conductive material, kneading the powder with a predetermined amount of solvent (eugenol, etc.), resin (ethyl cellulose, etc.) and dispersant using a planetary mixer, etc., and dispersing them using a three-roll mill, etc. In the preparation of the above-mentioned conductive paste, by adjusting the volume concentration of the conductive material relative to the total volume of the conductive material (typically silver powder) and the resin component in the conductive paste, i.e., PVC (pigment volume concentration), two conductive pastes having different shrinkage rates during calcination (high shrinkage conductive paste (A) and low shrinkage conductive paste (B)) are prepared. The shrinkage rate of the high shrinkage conductive paste due to firing is preferably 15% or more and 20% or less. The shrinkage rate of the low-shrinkage conductive paste due to firing is preferably 5% or more and 15% or less. The PVC of the high shrinkage conductive paste is preferably 60% or more and 80% or less. The PVC of the low-shrinkage conductive paste is larger than the PVC of the high-shrinkage conductive paste, and is preferably 80% or more and 90% or less. Here, the shrinkage rate can be determined by, for example, applying the conductive paste on a polyethylene terephthalate (PET) film, drying it, cutting it into a size of about 5 mm×5 mm, and then measuring the change in the sample size by thermomechanical analysis (TMA: thermomechanical analyzer). The PVC can be determined by measuring the weight ratio of the conductive material to the resin component by thermogravimetry (TG), and calculating from the densities of the conductive material and the resin component. (4) Preparation of resin paste A resin paste is prepared for forming the gap portion of the laminated coil component 1. The resin paste can be prepared by adding a resin (acrylic resin, etc.) that disappears during firing to a solvent (isophorone, etc.). (5) Fabrication of laminated coil components (5-1) Preparation of substrate First, prepare the ferrite sheet 31 ( Figure 4 (a) Figure 5 Here, Figure 4 This is a top view of the ferrite sheet from above. Figure 5 yes Figure 4 Cross-sectional view of a ferrite sheet. Next, the resin paste is printed on the portion where the first gap 21 is to be formed (i.e., the portion where the coil conductor layer is formed except for the lead portion and the via hole forming portion) to form a resin paste layer 32 ( Figure 4 (b) Figure 5 (b)). Next, the low shrinkage conductive paste is printed on the portion where the lead portion is to be formed, thereby forming a low shrinkage conductive paste layer 33 ( Figure 4 (c)). Next, the highly shrinkable conductive paste is printed on the entire area where the coil conductor layer 15 is to be formed, thereby forming a highly shrinkable conductive paste layer 34 ( Figure 4 (d) Figure 5 (d)). Figure 5 As shown in (d), the highly shrinkable conductive paste layer 34 covers the resin paste layer 32 and has an overhanging portion 36 at a location where the second cavity is to be formed. The width of the overhanging portion 36 is preferably 1.0 μm or more and 30.0 μm or less, more preferably 2.0 μm or more and 20.0 μm or less, and particularly preferably 2.0 μm or more and 10.0 μm or less. The thickness of the overhanging portion 36 is preferably 1.0 μm or more and 10.0 μm or less, more preferably 2.0 μm or more and 8.0 μm or less, and even more preferably 3.0 μm or more and 6.0 μm or less. The protruding portion 36 has a tapered shape toward the outside of the conductive paste layer. Figure 5 As shown in (d), the thickness of the extension portion 36 decreases toward the outside of the high shrinkage conductive paste layer 34 in the cross section perpendicular to the winding direction. By forming the coil conductor layer from the high shrinkage conductive paste, voids are formed in the extension portion by shrinkage during firing, thereby further suppressing the generation of cracks from the end of the coil conductor layer. The highly shrinkable conductive paste layer 34 may be formed using a printed plate having the shape of the extended portion 36 , or may be formed by applying the highly shrinkable conductive paste so as to spread from the resin paste layer 32 toward the ferrite sheet 31 . Next, the ferrite paste is printed on the region where the high shrinkage conductive paste layer 34 is not formed so as to have the same height as the high shrinkage conductive paste layer 34, thereby forming a ferrite paste layer 35 ( Figure 4 (e), Figure 5 (e)). Through the above steps, the first pattern sheet is formed. In addition, a ferrite sheet 41 is prepared. A via hole 42 ( Figure 6 (a)). Next, the resin paste is printed on the portion where the first gap 21 is to be formed, thereby forming a resin paste layer 43 ( Figure 6 (b)). Next, the highly shrinkable conductive paste is printed on the entire area where the coil conductor layer is to be formed, thereby forming a highly shrinkable conductive paste layer 44 ( Figure 6 (c)). Next, the ferrite paste is printed on the region where the high shrinkage conductive paste layer 44 is not formed so as to have the same height as the high shrinkage conductive paste layer 44, thereby forming a ferrite paste layer 45 ( Figure 6 (d)). Through the above steps, the second pattern sheet is formed. In addition, a ferrite sheet 51 is prepared, and a via hole 52, a resin paste layer 53, a high shrinkage conductive paste layer 54, and a ferrite paste layer 55 are formed in the same manner as the above-mentioned pattern sheet to obtain a third pattern sheet ( Figure 7 (a)~(d)). In addition, a ferrite sheet 61 is prepared, and a via hole 62, a resin paste layer 63, a low shrinkage conductive paste layer 64, a high shrinkage conductive paste layer 65, and a ferrite paste layer 66 are formed in the same manner as the above-mentioned pattern sheet to obtain a fourth pattern sheet ( Figure 8 (a)~(e)). The first to fourth pattern sheets produced as described above are stacked in sequence, and ferrite sheets without any printing are arranged on the upper and lower sides, and a laminate preform is produced by thermal compression bonding. At this time, in the method disclosed in the present invention, since there is no resin paste layer for forming the void portion on the side of the conductive paste layer where the stress is most concentrated during compression bonding, it is possible to suppress the generation of cracks due to different springback amounts. The laminate preform is cut into pieces by a cutting machine or the like. The obtained element is subjected to roller treatment to cut the corners of the element and form rounded corners. The roller treatment can be performed on the unfired laminate or the calcined laminate. In addition, the roller treatment can be either dry or wet. The roller treatment can be a method of rubbing the elements against each other or a method of roller treatment with a medium. After the drum treatment, the element is fired at a temperature of, for example, 880° C. to 920° C. to obtain the base 2 of the laminated coil component 1. The resin paste layer disappears by firing, forming the first gap 21. In addition, the silver paste shrinks by firing, and the extended portion of the silver paste layer shrinks and is introduced into the coil conductor side, forming the second gap 22. (5-2) Formation of External Electrodes Next, an Ag paste containing Ag and glass for forming external electrodes is applied to the end surface of the substrate 2 and fired to form a base electrode. Next, a Ni coating and a Sn coating are sequentially formed on the base electrode by electroplating to form external electrodes, thereby obtaining a Figure 1 The laminated coil component 1 is shown. The present disclosure provides a method for manufacturing a laminated coil component. Specifically, The stacked coil component includes: an insulator portion; a coil embedded in the insulator portion and electrically connected by a plurality of coil conductor layers; and an external electrode disposed on a surface of the insulator portion and electrically connected to the coil, a first gap portion being provided between the insulator portion and a main surface of the coil conductor layer, and a second gap portion extending horizontally outward from a side surface of the coil conductor layer at the same height as the first gap portion, The manufacturing method of the laminated coil component comprises the following steps: Prepare insulation sheets; forming a resin paste layer on the insulating sheet using a resin paste; forming a conductive paste layer using a conductive paste, the conductive paste layer covering the resin paste layer and having a protruding portion at a location where the second gap is formed; On the insulating sheet, forming an insulating paste layer using an insulating paste so that at least a portion of the upper surface of the conductive paste layer is exposed; A plurality of insulating sheets formed with the above-mentioned layers are stacked to form a stacked molded body in which the conductive paste layers are connected in a coil shape; The above-mentioned stacked compact is calcined. In a preferred embodiment, the conductive paste has a PVC of 60% to 80%. As mentioned above, although one embodiment of the present invention has been described, this embodiment can be modified in various ways. For example, in the above description, ferrite sheets corresponding to the respective insulating layers are prepared, the sheets are printed to form coil patterns, and these are crimped to obtain the element. However, the element may be obtained by sequentially printing all the layers. The laminated coil component manufactured by the method disclosed above is not prone to cracks and other undesirable conditions during manufacturing. In addition, the laminated coil component manufactured by the method disclosed above has a first gap portion 21 and a second gap portion 22, which is not prone to internal stress between the coil conductor layer and the insulator portion, or the internal stress is alleviated, so it is not prone to cracks and other undesirable conditions. Therefore, the present disclosure also provides a laminated coil component obtained by the above-mentioned manufacturing method. Specifically, the present disclosure provides a laminated coil component, comprising: an insulator portion; a coil embedded in the insulator portion and formed by electrically connecting a plurality of coil conductor layers; and an external electrode disposed on a surface of the insulator portion and electrically connected to the coil. The laminated coil component includes a first gap between the insulator portion and a main surface of the coil conductor layer. A second gap portion is provided at the same height as the first gap portion and extends outward in the horizontal direction from the side surface of the coil conductor layer. In the laminated coil component 1 of the present embodiment, the base body 2 is composed of the insulator portion 6 and the coil 7 . The insulator portion 6 may include a first insulator layer 11 and a second insulator layer 12 . The first insulating layer 11 is provided between the coil conductor layers 15 adjacent to each other in the stacking direction and between the coil conductor layer 15 and the upper surface or the lower surface of the base. The second insulating layer 12 is formed so that the upper surface ( Figure 2In other words, the second insulator layer 12 is formed to be located at the same height as the coil conductor layer 15 in the stacking direction. Figure 2 In the embodiment, the second insulating layer 12a is located at the same height as the coil conductor layer 15a in the stacking direction. In one embodiment, the second insulating layer 12 may be provided so that a part thereof overlaps the outer edge portion of the coil conductor layer 15. In other words, the second insulating layer 12 may be provided so as to cover the outer edge portion of the coil conductor layer 15. In one embodiment, when one coil conductor layer 15 and the second insulating layer 12 are viewed from above, the second insulating layer 12 may be present on the inner side than the outer edge of the coil conductor layer 15 . The first insulating layer 11 and the second insulating layer 12 may be integrated into the base 2 . In this case, it can be considered that the second insulating layer 12 exists at the same height as the coil conductor layer 15 . The insulator portion 6 is preferably made of a magnetic body, and more preferably made of sintered ferrite. The sintered ferrite contains at least Fe, Ni, and Zn as main components. The sintered ferrite may further contain Cu. The first insulator layer 11 and the second insulator layer 12 may have the same composition or different compositions. In a preferred embodiment, the first insulator layer 11 and the second insulator layer 12 have the same composition. In one embodiment, the sintered ferrite contains at least Fe, Ni, Zn, and Cu as main components. In the above-mentioned sintered ferrite, the Fe content converted into Fe2O3 may preferably be 40.0 mol% or more and 49.5 mol% or less (based on the total of main components, the same applies hereinafter), and more preferably 45.0 mol% or more and 49.5 mol% or less. In the sintered ferrite, the Zn content calculated as ZnO may be preferably 5.0 mol% to 35.0 mol% (based on the total of main components, the same applies hereinafter), and more preferably 10.0 mol% to 30.0 mol%. In the sintered ferrite, the Cu content is preferably 4.0 mol% to 12.0 mol% (based on the total of main components, the same applies hereinafter), and more preferably 7.0 mol% to 10.0 mol% in terms of CuO. In the above-mentioned sintered ferrite, the Ni content is not particularly limited, and may be the remainder of the above-mentioned other main components, namely, Fe, Zn, and Cu. In one embodiment, in the above-mentioned sintered ferrite, Fe is converted into Fe2O3 of 40.0 mol% or more and 49.5 mol% or less, Zn is converted into ZnO of 5.0 mol% or more and 35.0 mol% or less, Cu is converted into CuO of 4.0 mol% or more and 12.0 mol% or less, and NiO is the remainder. In the present disclosure, the above-mentioned sintered ferrite may further contain additives. Examples of additives in the sintered ferrite include, but are not limited to, Mn, Co, Sn, Bi, and Si. The content (addition amount) of Mn, Co, Sn, Bi, and Si is preferably 0.1 parts by weight or more and 1 part by weight or less, respectively, relative to a total of 100 parts by weight of the main components (Fe (converted into Fe2O3), Zn (converted into ZnO), Cu (converted into CuO), and Ni (converted into NiO)). In addition, the above-mentioned sintered ferrite may further contain impurities that are unavoidable in manufacturing. As described above, the coil 7 is configured by being electrically connected to each other in a coil shape through the coil conductor layers 15. The coil conductor layers 15 adjacent to each other in the stacking direction are connected by via-hole conductors penetrating the insulator portion 6. The material constituting the coil conductor layer 15 is not particularly limited, but examples thereof include Au, Ag, Cu, Pd, Ni, etc. The material constituting the coil conductor layer 15 is preferably Ag or Cu, more preferably Ag. The conductive material may be only one kind or two or more kinds. The via hole conductor is provided so as to penetrate the first insulating layer 11. The material constituting the via hole conductor may be the material described for the coil conductor layer 15. The material constituting the via hole conductor may be the same as or different from the material constituting the coil conductor layer 15. In a preferred embodiment, the material constituting the via hole conductor is the same as the material constituting the coil conductor layer 15. In a preferred embodiment, the material constituting the via hole conductor is Ag. In the coil 7, the thickness of the coil conductor layer 15 in the lead portion is greater than that in the winding portion. By increasing the thickness of the coil conductor layer in the lead portion, the adhesion between the coil conductor layer and the insulator portion in the lead portion can be improved. In this embodiment, the coil conductor layer 15 of the lead portion of the coil 7 is stacked with a low shrinkage layer (corresponding to the low shrinkage conductive paste layer 33, 64) having a smaller shrinkage rate during firing and a high shrinkage layer (corresponding to the high shrinkage conductive paste layer 34, 65) having a larger shrinkage rate. By stacking the low shrinkage layer with a smaller shrinkage rate during firing on the lead portion, shrinkage during firing can be suppressed, making it difficult to generate a gap between the coil conductor layer of the lead portion and the insulator portion, thereby improving the close contact between the coil conductor layer of the lead portion and the insulator portion. On the other hand, the coil conductor layer 15 of the winding portion of the coil 7 may be a high shrinkage layer having a large shrinkage rate during calcination. By calcining the coil conductor layer 15 of the winding portion as a high shrinkage layer having a large shrinkage rate during calcination, the stress relaxation space, namely the first gap portion 21 and the second gap portion 22, can be formed more reliably. In one embodiment, the low shrinkage layer is formed of a material having a shrinkage rate of 5% or more and 15% or less due to firing. In one embodiment, the high shrinkage layer is formed of a material having a shrinkage rate by firing that is greater than that of the low shrinkage layer and is 15% to 20%. The thickness ratio of the low shrinkage layer to the high shrinkage layer in the coil conductor layer 15 of the lead portion (low shrinkage layer / high shrinkage layer) may preferably be 0.2 to 1.8, and more preferably 0.2 to 0.8. The first gap portion 21 and the second gap portion 22 function as so-called stress relaxation spaces. The first gap 21 is provided between the insulator portion 6 and the main surface of the coil conductor layer 15. Here, the main surface of the coil conductor layer refers to two surfaces perpendicular to the stacking direction of the stacked coil component. Figure 2 As shown, the first gap portion 21 is provided between the first insulating layer 11 and the lower main surface of the coil conductor layer 15 . The width of the first gap 21 ( Figure 3 W2) is preferably 10 μm to 200 μm, more preferably 30 μm to 150 μm, and further preferably 50 μm to 100 μm. Here, the width of the first gap portion refers to the width in a direction perpendicular to the winding direction of the coil and perpendicular to the stacking direction, and the width of the widest part. The width of the first gap 21 is equal to the width of the coil conductor layer 15 ( Figure 3 The ratio of the width of the void portion (W2) / the width of the conductor layer (W3)) can be preferably greater than or equal to 0.1 and less than or equal to 0.9, more preferably greater than or equal to 0.2 and less than or equal to 0.8, and further preferably greater than or equal to 0.3 and less than or equal to 0.7. The thickness of the first gap 21 ( Figure 3 T2) in the above is preferably 1.0 μm or more and 10.0 μm or less, and more preferably 3.0 μm or more and 8.0 μm or less. Here, the thickness of the first gap portion refers to the thickness in the stacking direction and is the average value of the thickness of the portion divided into five equal parts in the width direction. The second gap portion 22 is adjacent to the side surface of the coil conductor layer 15 and is arranged at the same height as the first gap portion. The second gap portion 22 extends outward in the horizontal direction from the side surface of the coil conductor layer 15. Here, the side surface of the coil conductor layer refers to two surfaces that are parallel to the winding direction of the coil and different from the main surface. The same height refers to the same height when the stacking direction is used as the height. For example, in the present embodiment, it refers to being formed on the same ferrite sheet. The horizontal direction refers to the direction of the surface perpendicular to the stacking direction, and the horizontal outer side refers to the direction vertically away from the side surface of the coil conductor layer along the surface perpendicular to the stacking direction. The width of the second gap 22 ( Figure 3 W1) is preferably 1.0 μm or more and 30.0 μm or less, more preferably 2.0 μm or more and 20.0 μm or less, and particularly preferably 2.0 μm or more and 10.0 μm or less. Here, the width of the second gap portion refers to the width in a direction perpendicular to the winding direction of the coil and perpendicular to the stacking direction, and the width of the widest part thereof. The thickness of the second gap 22 ( Figure 3 T1) is preferably 1.0 μm to 10.0 μm, more preferably 2.0 μm to 8.0 μm, and even more preferably 3.0 μm to 6.0 μm. Here, the thickness of the second gap portion refers to the thickness in the stacking direction and the thickness of the thickest portion. The width and thickness of the above-mentioned gap portion can be measured as follows. The LT surface of the chip is polished with the polishing paper facing the surface, and the polishing is stopped at the W-inch center of the coil conductor layer. Then, the chip is observed using a microscope. The width and thickness of the gap located at the L-inch center of the coil conductor layer are measured using the measurement function attached to the microscope. The second gap 22 has a tapered shape facing outward. Figure 3 As shown, the thickness of the second gap 22 decreases as it becomes farther away from the coil conductor layer 15. When the second gap has such a shape, the occurrence of cracks in the element can be further suppressed. The external electrodes 4 and 5 are provided so as to cover both end surfaces of the substrate 2. The external electrodes are made of a conductive material, preferably one or more metal materials selected from Au, Ag, Pd, Ni, Sn and Cu. The external electrode may be a single layer or a multi-layer. In one embodiment, the external electrode may be a multi-layer, preferably 2 or more layers and 4 or less layers, for example 3 layers. In one embodiment, the external electrode is multilayered and may include a layer containing Ag or Pd, a layer containing Ni, or a layer containing Sn. In a preferred embodiment, the external electrode is composed of a layer containing Ag or Pd, a layer containing Ni, and a layer containing Sn. Preferably, the layers are arranged in the order of a layer containing Ag or Pd, preferably a layer containing Ag, a layer containing Ni, and a layer containing Sn from the coil conductor layer side. Preferably, the layer containing Ag or Pd is a layer sintered with Ag paste or Pd paste, and the layer containing Ni and the layer containing Sn may be a plated layer. The laminated coil component disclosed in the present invention preferably has a length of 0.4 mm to 3.2 mm, a width of 0.2 mm to 2.5 mm, and a height of 0.2 mm to 2.0 mm, and more preferably has a length of 0.6 mm to 2.0 mm, a width of 0.3 mm to 1.3 mm, and a height of 0.3 mm to 1.0 mm. [Example] Example Preparation of ferrite paste The powders of Fe2O3, ZnO, CuO and NiO were weighed in such a manner that the total amount thereof was 49.0 mol%, 25.0 mol%, 8.0 mol% and the remainder, respectively. These powders were put into a ball mill together with a PSZ medium, pure water and a dispersant, mixed and crushed in a wet manner, dried, and calcined at 700°C to obtain a calcined powder. A ferrite paste was prepared by adding a predetermined amount of a ketone solvent, polyvinyl acetal and an alkyd plasticizer to the calcined powder, kneading them with a planetary mixer, and further dispersing them with a three-roll mill. Preparation of ferrite sheets The ferrite material is weighed to have the same composition as the above-mentioned ferrite paste. The weighed material is put into a ball mill together with a PSZ medium, pure water, and a dispersant, mixed and crushed in a wet manner, and then dried and calcined at a temperature of 700°C to obtain a calcined powder. Polyvinyl butyral organic binder, ethanol, and toluene are added to the obtained calcined powder, and the obtained mixture is put into a pot mill together with PSZ balls for mixing and crushing. The obtained mixture is formed into sheets using a scraper method to make ferrite sheets. Preparation of conductive paste for coil conductors A predetermined amount of silver powder was prepared as a conductive material, and the silver powder was kneaded with eugenol, ethyl cellulose, and a dispersant using a planetary mixer, and then dispersed using a three-roll mill to prepare a conductive paste for a coil conductor. In the preparation of the conductive paste described above, two types of conductive pastes (A) and (B) having different shrinkage ratios during firing were prepared by adjusting PVC. (A) High shrinkage conductive paste (shrinkage rate is 15% at 800°C) (B) Low shrinkage conductive paste (shrinkage rate is 10% at 800°C) Preparation of resin paste The resin paste is made by mixing acrylic resin with isophorone. Production of laminated coil components The ferrite sheet, ferrite paste, high shrinkage conductive paste, low shrinkage conductive paste and resin paste are used as described above. Figures 4 to 8 The steps shown are to prepare pattern sheets, and to press-bond them to obtain a laminate preform as an aggregate. Next, the laminate preform is cut by a cutter or the like to separate the elements. The obtained elements are subjected to a roller treatment to cut the corners of the elements and form rounded corners. After the roller treatment, the elements are calcined at a temperature of 920° C. to obtain a matrix. Next, an Ag paste containing Ag and glass for forming external electrodes is applied to the end surface of the substrate and sintered to form a base electrode. Next, a Ni coating and a Sn coating are sequentially formed on the base electrode by electroplating to form external electrodes, thereby obtaining a laminated coil component of the embodiment. Comparative Example A laminated coil component of the comparative example was obtained in the same manner as in the above-described embodiment, except that the conductive paste layer was directly formed on ferrite sheets 31 , 41 , 51 , 61 instead of resin paste layer 32 , 43 , 53 , 63 , and the resin paste layer was formed to cover the conductive paste layer. The samples (laminated coil components) in the examples and comparative examples all had L (length) = 1.0 mm, W (width) = 0.5 mm, and T (height) = 0.5 mm. evaluate The presence or absence of cracks was evaluated for each of 100 laminated coil components of the embodiment and comparative example obtained above. The results are shown in the following table. The LT surface was polished, the polishing was stopped at approximately the center, and the polished surface was observed using a digital microscope to confirm the presence or absence of cracks.
Table 1
Claims
1. A laminated coil component, comprising: Insulator part; A coil, embedded in the insulator portion and formed by electrically connecting a plurality of coil conductor layers; and an external electrode, which is provided on the surface of the insulator portion and is electrically connected to the coil, wherein the laminated coil component is characterized in that: The plurality of coil conductor layers include at least one first coil conductor layer, A first gap is provided between the insulator portion and the main surface of the first coil conductor layer. A second gap portion is provided at the same height as the first gap portion and extends outward in the horizontal direction from the side surface of the first coil conductor layer. The first gap portion and the second gap portion are spaced apart.
2. The laminated coil component according to claim 1, wherein: The thickness of the first coil conductor layer is greater than or equal to 1.0 μm and less than or equal to 90.0 μm.
3. The laminated coil component according to claim 1 or 2, characterized in that: A ratio of a width of the first gap portion to a width of the first coil conductor layer is greater than or equal to 0.1 and less than or equal to 0.
9.
4. The laminated coil component according to claim 1 or 2, characterized in that: The thickness of the first cavity is greater than or equal to 1.0 μm and less than or equal to 10.0 μm.
5. The laminated coil component according to claim 1 or 2, characterized in that: The second cavity has a thickness of 1.0 μm or more and 10.0 μm or less.
6. The laminated coil component according to claim 1 or 2, characterized in that: The width of the second gap is greater than or equal to 1.0 μm and less than or equal to 30.0 μm.
7. The laminated coil component according to claim 1 or 2, characterized in that: The second gap has a tapered shape extending from the coil conductor layer toward the outside.
Citation Information
Patent Citations
Laminated coil component and manufacturing method thereof
JP2018011014A